Lee Jen Sen develops Over-Speed Detection System Project, wins UMPSA Gold Award - Shalfarina, Shahriman (UMPSA, 2024)
GAMBANG, 25 October 2024 – Hard work and perseverance—these are the principles practised by Lee Jen Sen, 21, to achieve success in his studies.